Oxygen Isotopic Composition of Fallen Snow in Antarctica (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Kikuo KATO (National Institute of Polar Research, 1979)
The transportation process of water vapor to the Antarctic ice sheet is one of the most important factors controlling oxygen isotopic composition of precinitation in Antarctica, which was related only to its temperature of formation in the previous studies. The relationship between the oxygen isotopic composition of fallen snow at Syowa Station and the transportation process of water vapor to the Antarctic ice sheet has been investigated in this study. It was found that the oxygen isotopic composition of fallen snow is largely controlled by the supply of ^O-rich water vapor resulting from the approach of a circumpolar cyclone, and is closely related to the distance between the open sea and the sampling station, Taking into consideration the transportation process of water vapor to the Antarctic ice sheet, the correlation between the temperature of formation and the oxygen isotopic composition of fallen snow provides information about the formation process of snow. The correlation between the monthly means of the oxygen isotopic composition of fallen snow and the surface air temperature also provides information about the formation process of snow.